Lista de deportados (para Angra do Heroísmo) (1930)
Deportados em Angra do Heroísmo: José de Almeida; Jaime Rebelo; Francisco dos Santos Violante; Jorge da Silva; Cândido Marques da Silva; Alexandrino Costa; António Mendes Soldado Jr.; José Francisco dos Santos; Raul de Sousa; José Severe dos Santos; Leonel Frade; Artur Duarte; Leonel das Dores Ferro Alves; Eduardo de Faria; José Maria Vingre Preto da Cruz